Small-scale fisheries access to fishing opportunities in the European Union: is the common fisheries policy the right step to SDG14b? - Said, A.; Pascual-Fernánd, J.ez; Amorim, V.; Autzen, M.; Hegland, T.; Pita, C.; Ferretti, J.; Penca, J. (Marine Policy, 2020)
The profile of small-scale fisheries has been raised through a dedicated target within the United Nations Sustainable Development Goals (SDG14b) that calls for the provision of ‘access of small-scale artisanal fishers to marine resources and markets’. By focusing on access to fisheries resources in the context of European Union, in this article we demonstrate that the potential for small-scale fishing sectors to benefit from fishing opportunities remains low due to different mechanisms at play including legislative gaps in the Common Fisheries Policy, and long-existing local structures somewhat favouring the status quo of distributive injustice. Consequently, those without access to capital and authority are faced by marginalizing allocation systems, impacting the overall resilience of fishing communities. Achieving SDG14b requires an overhaul in the promulgation of policies emanating from the present nested governance systems.